2006
DOI: 10.1007/s00127-006-0037-3
|View full text |Cite
|
Sign up to set email alerts
|

Stressors and psychological symptoms in students of medicine and allied health professions in Nigeria

Abstract: Several identified stressors such as financial problems, academic pressures and their consequent effect on social life have an adverse effect on the mental health of students in this environment especially for students of medicine and dentistry. While stressors outside the reach of the school authorities are difficult to control, academic support including providing a conducive learning environment, advice on means for sustenance, added support during periods of transition are key areas for interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
77
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(97 citation statements)
references
References 17 publications
14
77
0
2
Order By: Relevance
“…13,22,23 In this study, only females showed a strong association with common mental disorder after logistic regression. This finding coincides with the literature that asserts that women have higher prevalence of mental disorders and that CMD is the third health problem among females in developed countries and the fifth in undeveloped countries.…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…13,22,23 In this study, only females showed a strong association with common mental disorder after logistic regression. This finding coincides with the literature that asserts that women have higher prevalence of mental disorders and that CMD is the third health problem among females in developed countries and the fifth in undeveloped countries.…”
Section: Resultsmentioning
confidence: 50%
“…These stressful factors include the proximity of death and innumerous pathological processes, excessive workload, competitiveness, fear of making mistakes, late financial independence and disappointment with the course, as well as privation of the family conviviality and leisure. 18,23,28,29 Sleep problems have been associated with deficits in attention and academic performance, After adjustment using multiple logistic regression analysis, the following variables were associated with common mental disorder: female sex, not having good expectations for the future, not seeing the course as a source of pleasure and considering oneself emotionally tense (Table 3). The general prevalence of common mental disorder among the students was higher than the rates found in general populations studied in industrialized countries.…”
Section: Resultsmentioning
confidence: 99%
“…Some (17,(19)(20)(22)(23)(25)(26) analysed the relationship between stress and physiological or psychological manifestations, and others (10,12,21,24,(27)(28) explored the general health state of the students involved in the researches.…”
Section: Resultsmentioning
confidence: 99%
“…Students more frequently reported as stress-related factors a noisy environment, lack of safety, and transportation means. Authors still report that gender was not a significant factor for the psychological morbidity (23) . As to the physiological stress manifestations, researchers collected saliva samples from students, and requested them to answer a questionnaire in three different occasions: a month after the beginning of the semester, after the final exams, and after the grades had been published.…”
Section: Discussionmentioning
confidence: 96%
“…(5,6) Studies have also suggested high levels of stress in health care profession students. (7) Especially, considerable amount of stress has been noted in medical students. (8) The source of stress could be from anywhere.…”
Section: Introductionmentioning
confidence: 99%